Опера. Волки: [роман] / Евгений Сухов - Сухов Евгений (Опера, 2005)
Экземпляры: ф.13 (2006) / Инвентарный номер: 50093 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 91 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44